HABITAT KELELAWAR BUAH (Dobsonia minor) DI HUTAN TROPIS DATARAN RENDAH NUNI PANTAI UTARA MANOKWARI (Habitat of Fruit Bats (Dobsonia minor) in Nuni Tropical Lowland Forest of Northern Area in Manokwari) - Sepus M. Fatem; Petrus Izak Bumbut; Antoni Ungirwalu (Media Konservasi, 2006)
This research has been done in a cave ecosystem at Nuni tropical lowland forest in the northern coastal area of Manokwari, from 21 - 25 May 2005. A descriptive method with the observation technique has been used. The research's stages are; preliminary survey outside the cave's ecosystem to get an easy and proper observation plant for the surronding vegetation. While a survey inside the cave (interior survey) aims to describe the climatic condition, cave's shape and other ecological aspects. The result indicates that this cave ecosystem is located in the northern coastal area of Manokwari or exactly at the coordinate 00º46,778 South lattitude and 133º55.928 East langitude, at the altitude of 210 metre above sea level. The fruit bats in the Lowland forest of Nuni use this cave as roosting site during the day. The length of this cave is around 800 metre in the form of a tunnel, the height is 8 metre and the floor consist of sharp pointed rocks. The microclimate within the cave has an average temperature of 30º C, the relative humidity 81 % while the condition outside the cave; the average temperature is 29.3º C and relative humidity is 82 %. The total plant species found arround the bat's cave is 36 species from 27 families, the distribution based on their life stages are; seedlings 22 species, sapplings 15 species, poles 14 species and trees 12 species. The amount of the vegetation, ecologically support significantly the development and existence of these fruit bats.Keyword: Tropical Forest of Nuni, Dobsonia minor